Perancangan Front End Website dengan Memanfaatkan Template Bootstrap di Diskominfo Kabupaten Garut (Current Research in Education: Conference Series Journal, 2023)
Front end website is one of the main points in designing a website. In this study, a front end website was designed by using a bootstrap template. In designing the front end website, the researcher uses quantitative research methods by distributing surveys related to the use of bootstrap templates in designing the front end website. Then testing the results of the front end website design by Diskominfo Garut Regency. The purpose of this study is to compare the results of the survey with testing the use of bootstrap templates in designing the front end of the website. Therefore, it is known that the survey results and test results for the front end website design are appropriate. So the bootstrap template is very influential on the process and work of designing the front end website at Diskominfo Garut Regency.